A pilot study assessing the spiritual, emotional, physical/environmental, and physiological needs of mechanically ventilated surgical intensive care unit patients via eye tracking devices, head nodding, and communication boards. Issue 1 (19th September 2018) - Duffy, Erin I; Garry, Jonah; Talbot, Lillian; Pasternak, David; Flinn, Ashley; Minardi, Casey; Dookram, Michele; Grant, Kathleen; Fitzgerald, Debbie; Rubano, Jerry; Vosswinkel, James; Jawa, Randeep S
Abstract : Background: Mechanically ventilated patients in the intensive care unit (ICU) are unable to communicate verbally. We sought to evaluate their needs via a communication board (CB) and a novel eye tracking device (ETD) that verbalizes selections made by gazing. Methods: This was a pilot prospective study conducted in a tertiary care surgical ICU. Continuously mechanically ventilated adult surgical ICU patients with a Richmond Agitation-Sedation Scale score of −1 to +1, without cognitive impairment, were eligible. We asked patients four yes-or-no questions to assess basic needs regarding presence of pain, need for endotracheal suction, satisfactory room temperature, and position comfort. Patients were then asked if there was anything else that they wanted to communicate. All responses were confirmed by head nodding. Results: The median accuracy of the CB (100% (IQR 100%–100%)) for basic needs communication (yes/no questions) was comparable with that of the ETD (100% (IQR 68.8%–100%); p=0.14) in the 12 enrolled patients. Notably, 83% of patients desired to communicate additional information, ranging from spiritual (eg, desire for prayer/chaplain), emotional (eg, frustration, desire for comfort), physical/environmental (eg, television), to physiological (eg, thirst/hunger) needs. Discussion: The majority of patients desired to communicate something other than basic needs. Unless specifically assessed via an assistive communication device (eg, CB or ETD), some of these other needs would have been difficult to discern. Level of evidence: IV therapeutic care/management.